1987
DOI: 10.1246/bcsj.60.420
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Oxidation of Thiols by Coenzyme PQQ

Abstract: Kinetic studies on the oxidation of thiols by coenzyme PQQ are carried out under anaerobic conditions. A bell shaped pH-rate profile having a maximum rate at around pKa of the thiol is observed. The rate-determining step changes between acidic and basic sides of the profile indicating the existence of at least one intermediate in the course of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The scheme of the reduction of PQQ by PhSH was discussed by Itoh et al As they reported, one of the possible mechanisms is that involving C-5 attack of the thiolate ion followed by breakdown to reduced PQQ and the corresponding disulfide (see the scheme in ref 32). concentration of GSH of 9.60 × 10 -3 M).…”
Section: Resultsmentioning
confidence: 99%
“…The scheme of the reduction of PQQ by PhSH was discussed by Itoh et al As they reported, one of the possible mechanisms is that involving C-5 attack of the thiolate ion followed by breakdown to reduced PQQ and the corresponding disulfide (see the scheme in ref 32). concentration of GSH of 9.60 × 10 -3 M).…”
Section: Resultsmentioning
confidence: 99%
“…Free PQQ has been shown to catalyze non-enzymatic reactions, including the oxidation of thiols to disulfide [24,25]. Taking advantage of the latter together with its redox property, PQQ has been applied for electrochemical detection of thiols [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases the o-quinone moiety serves as an efficient electron shuttle without deactivation of the electrocatalyst. This unique combination of properties is attributed to the substituted o-quinone ring found in PQQ and TTQ that impedes 1,4-addition of nucleophiles.Interestingly, PQQ catalyzes non-enzymatic reactions such as the oxidation of thiols to disulfides [11,12], which we have utilized to develop sensitive and selective thiol detection strategies with PQQ entrapped in a polypyrrole conducting polymer membrane [7][8][9][10].As part of an effort to harness the electrocatalytic properties of the natural o-quinone cofactors, we have initiated research to synthesize o-quinone analogues with exceptional redox cycling capabilities similar to PQQ [13]. One challenge with this approach is maintaining electrocatalyst levels in the sensing membrane for extended time periods.…”
mentioning
confidence: 99%